Effective passivation of crystalline silicon surfaces by ultrathin atomic-layer-deposited TiOx layers. (September 2017) - Titova, Valeriya; Veith-Wolf, Boris; Startsev, Dimitrij; Schmidt, Jan
Abstract: We characterize the surface passivation properties of ultrathin titanium oxide (TiOx ) films deposited by atomic layer deposition (ALD) on crystalline silicon by means of carrier lifetime measurements. We compare different silicon surface treatments prior to TiOx deposition, such as native silicon oxide (SiOy ), chemically grown SiOy and thermally grown SiOy . The best passivation quality is achieved with a native SiOy grown over 4 months and a TiOx layer thickness of 5 nm, resulting in an effective lifetime of 1.2 ms on 1.3 Ωcm p-type float-zone silicon. The measured maximum lifetime corresponds to an implied open-circuit voltage ( iV oc ) of 710 mV. For thinner TiOx layers the passivation quality is reduced, however, samples passivated with only 2 nm of TiOx still show a lifetime of 612 μs and an iV oc of 694 mV. The contact resistivity of the TiOx including the SiOy interlayer between the silicon wafer and the TiOx is below 0.8 Ωcm 2 . The combination of excellent surface passivation and low contact resistivity has the potential for silicon solar cells with efficiencies exceeding 26%.